Why epilepsy challenges social life. (January 2017) - Steiger, Bettina K.; Jokeit, Hennric
Highlights: People with epilepsy are at risk for reduced social competences and quality of life. Neuropsychological deficits in social cognition may impede social interactions. New diagnostic and therapeutic approaches are needed for better assessment and care. Abstract: Social bonds are at the center of our daily living and are an essential determinant of our quality of life. In people with epilepsy, numerous factors can impede cognitive and affective functions necessary for smooth social interactions. Psychological and psychiatric complications are common in epilepsy and may hinder the processing of social information. In addition, neuropsychological deficits such as slowed processing speed, memory loss or attentional difficulties may interfere with enjoyable reciprocity of social interactions. We consider societal, psychological, and neuropsychological aspects of social life with particular emphasis on socio-cognitive functions in temporal lobe epilepsy. Deficits in emotion recognition and theory of mind, two main aspects of social cognition, are frequently observed in individuals with mesial temporal lobe epilepsy. Results from behavioural studies targeting these functions will be presented with a focus on their relevance for patients' daily life. Furthermore, we will broach the issue of pitfalls in current diagnostic tools and potential directions for future research. By giving a broad overview of individual and interpersonal determinants of social functioning in epilepsy, we hope to provide a basis for future research to establish social cognition as a key component in the comprehensive assessment and care of those with epilepsy.